BEBERAPA PERSOALAN HUKUM SEPUTAR TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERSEROAN DALAM PERUNDANG-UNDANGAN EKONOMI INDONESIA - Erawaty, A.F. Elly (Jurnal Legislasi Indonesia, 2009)
Article 74 of the Company Act Number 40 of the year 2007states that the concept of Corporate Social Responsibility is amandatory and must be exercised by companies that activatingin the natural recourses sector. This concept will also beelaborated and regulated further by a Government Regulation.To anticipate the issuance of such regulation, the author ofthis article argues that there are some basic legal problemsthat should be dealt first. These problems are (a) the exactmeaning of ‘company that activating in the natural resources’,or in the other words, the kind of companies that must observesthe legal obligation to implement CSR (b) the necessity toharmonise and to synchronise some articles of several lawsand regulations that also deal with the issue of CSR (c) thelegal sanction for companies which disobeying the legalobligation of CSR, and (d) the overlapping of the CSR as legalobligation for private companies and the CSR whichspecifically designed for state-owned companies, known asProgram Kemitraan dan Bina Lingkungan (PKBL). To analysethese problems, the author examines also the decision of theMahkamah Konstitusi Number 53/PUU-VI/2008 dated on April15, 2009 which deciding the compatibility of Article 74 of theCompany Act with the basic legal norm of the IndonesianConstitution of 1945.